Aplikasi linoit sebagai basis dokumen portofolio pembelajaran bahasa jerman di SMA - Abdillah, Hamdan Khoiru; Ardiyani, Dewi Kartika (Fakultas Sastra, 2023)
Abstrak: The authentic assessment approach is important to be used in learning German in high school. This is based on the fact that the purpose of authentic assessment is not only to test the knowledge that has been learned, but also integrated as part of the learning process, so that cognitive ability is not the only consideration that must be considered, but also pay attention to skills and positive attitudes. Authentic assessment has several types, one of which is portfolio assessment. In today's technological development, portfolio assessment can be done digitally or called E-Portfolio. In general, the concept of purpose, pedagogical, and assessment in the implementation of these assessments remains the same as traditional paper-based portfolios although using the term E-Portfolio. The purpose of using an E-Portfolio is to make it easier to provide feedback, file collection, easier to navigate, and the ability to include achievements and evidence of learning more efficiently, flexibly, and easily modified. One of the digital media that can be used as a means of E-Portfolio assessment is the Linoit website-based media. Kata Kunci: authentic, e-portfolio, linoit, assessment